2013
DOI: 10.1371/journal.pone.0076854
|View full text |Cite
|
Sign up to set email alerts
|

Par6b Regulates the Dynamics of Apicobasal Polarity during Development of the Stratified Xenopus Epidermis

Abstract: During early vertebrate development, epithelial cells establish and maintain apicobasal polarity, failure of which can cause developmental defects or cancer metastasis. This process has been mostly studied in simple epithelia that have only one layer of cells, but is poorly understood in stratified epithelia. In this paper we address the role of the polarity protein Partitioning defective-6 homolog beta (Par6b) in the developing stratified epidermis of Xenopus laevis. At the blastula stage, animal blastomeres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Interestingly, it was demonstrated that in Xenopus epidermis, Par6b autonomously regulates the dynamics of apicobasal polarity, as it is required to maintain the “basolateral” state in both epidermal layers. This supports the idea that the Nichoid recapitulates the characteristics of a Niche-like structure [ 95 ] ( Figure 6 A). Itga6 (integrin alpha 6) was found downregulated by log 2 FC= −1.56 in NPCs grown inside the Nichoid ( Figure 6 A).…”
Section: Resultssupporting
confidence: 87%
“…Interestingly, it was demonstrated that in Xenopus epidermis, Par6b autonomously regulates the dynamics of apicobasal polarity, as it is required to maintain the “basolateral” state in both epidermal layers. This supports the idea that the Nichoid recapitulates the characteristics of a Niche-like structure [ 95 ] ( Figure 6 A). Itga6 (integrin alpha 6) was found downregulated by log 2 FC= −1.56 in NPCs grown inside the Nichoid ( Figure 6 A).…”
Section: Resultssupporting
confidence: 87%
“…Midguts were fixed in 4% PFA at RT for 2 hrs or at 4°C overnight. For vibratome sectioning, fixed midguts were embedded in 4–6% low-melting point agarose and sectioned at thickness of 100μm as previously described (Wang et al, 2013). Vibratome sections were permeabilized in 0.5% TritonX-100 in PBS for 20 min at RT while rocking and washed with PBS 5 min, three times.…”
Section: Star Methodsmentioning
confidence: 99%
“…Despite substantial differences in the mechanisms that establish radial polarity in frog and worm embryos, the PAR proteins aPKC and Par6b develop an analogous localization to the apical cortex in Xenopus ( Chalmers et al, 2003 ; Wang et al, 2013 ). aPKC promotes the localization of apical polarity regulator Crb3/Crumbs and antagonizes the localization of basolateral regulators Par1 and Lgl2 ( Fig.…”
Section: Xenopusmentioning
confidence: 99%